Conversationalism as an emerging method of thinking in and beyond African philosophy - Chimakonam, Jonathan O. (Acta Academica: Critical views on society, culture and politics, 2017)
In this paper, I employ an under-explored sub-Saharan African notion of ‘relationship’ to formulate a method that could ground discourses in African and intercultural philosophies. I claim that conversationalism, as the method is called, which is a new idea in African philosophy, might be an attractive model for thought if we take seriously the demand for equal and horizontal engagement especially in the field of intercultural philosophy. To do this, I will show what the method of conversationalism might look like in application. I will articulate a principle called Context-dependence of Value (CdV) that attempts to shift the paradigm of the truth of our propositions from the ‘facts’ which such ‘propositions’ assert to the ‘context’ in which those propositions are asserted, to show not only what makes conversationalism new but to also provide strong arguments on what makes it ultimately desirable for intercultural discourse and particularly now that some thinkers are calling for the decolonisation and Africanisation of philosophy.